PENAMBAHAN NANOPARTIKEL TITANIUM DIOKSIDA TERHADAP KEKUATAN FLEKSURAL DAN KEKERASAN BASIS GIGI TIRUAN RESIN AKRILIK POLIMERISASI PANAS - Manik, Siska Desyani; Tarigan, Slamat (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Heat polymerized acrylic resin is one of the polymers commonly used in dentistry included denture base materials because their manipulation, finishing, and polishing are easy and do not require expensive equipment. However, heat-polymerized acrylic resin denture bases also have several disadvantages including, low mechanical properties such as flexural strength and hardness. This study aims to determine the effect of adding titanium dioxide nanoparticles on the flexural strength and hardness of the heat polymerized acrylic resin denture base. Method: This type of research is an experimental laboratory with a sample size of 50mm x 10mm x 3mm for flexural strength test and 25mm x 10mm x 3mm for hardness test. The total sample of 48 samples consisted of the control group, the group with theÂ addition of titanium dioxide nanoparticles with concentrations of 0,5%, 1%, and 1,5%. Results: The highest mean value of flexural strength was in the group of adding titanium dioxide nanoparticles with a concentration of 1% and the lowest was the control group. The highest mean value of hardness was in the group of adding titanium dioxide nanoparticles with the concentration of 1,5% and the lowest was the control group. Based on ANOVA test results, there was a significant effect of adding titanium dioxide nanoparticles with a concentration of 0,5%, 1%, and 1,5% on the flexural strength and hardness of the heat polymerized acrylic resin denture base. Conclusion: The addition of titanium dioxide nanoparticles can increase the flexural strength and hardness of the heat polymerized acrylic resin denture base. The addition of titanium dioxide nanoparticles to heat polymerized acrylic resin denture base recommended by the researchers was with a concentration of 1%.